DOCKING MOLEKULER SENYAWA B-KAROTEN DALAM TANAMAN KELOR (Moringa Oleifera L.) SEBAGAI PENGHAMBAT ENZIM TIROSINASE DENGAN AUTODOCK – VINA - Bayu Herdi Al Huda; Nining Sugihartini; Hari Susanti; Dwi Utami (Jurnal Insan Farmasi Indonesia, 2020)
Hydroquinone has been used in cosmetics because of its whitening activity. In previous studies, B-carotene in Moringa plants was also known as an inhibitor of the tyrosinase enzyme. It is necessary to know how the interaction mechanism of B-carotene with tyrosinase (5M8N) and which compounds between hydroquinone and B-carotene provide computationally better activity as whitening. Tyrosinase was prepared using Discovery Studio Visualizer. Ligands were prepared using Autodock 4.2. Autodock-Vina is used for ligand docking between proteins. The result is the binding affinity (kcal/mol) of the ligand to protein. Visualization of docking between ligands and proteins using the Ligplot + Program with a 1 year license. Media used for the docking process is a computer with an Intel Core i7-3770 CPU with a speed of 3.40 GHz 8 cores, 1920x1080p resolution, VGA NVIDIA GeForce GTX 750, 8 GB RAM, Windows 8 64-bit. The docking results showed that the binding affinity of B-carotene to tyrosinase was -11.2 while hydroquinone with tyrosinase was -5.4 with RMSD 0. The results of visualization showed that B-carotene binds more amino acid receptors than hydroquinone. B-carotene in moringa has been shown to be active not only in wet laboratories, but also in dry laboratories.